Atratividade e palatabilidade de hidrolisados proteicos líquidos e secos e de aminoácidos para alevinos de dourado (Salminus brasiliensis) - Hattori, Jahina Fagundes de Assis (2022)
This study was carried out to determine the palatability of Dourado fingerlings (Salminus brasiliensis) fed diets containing different hydrolyzed liquid and dry proteins, whole protein, and amino acids compared to fish meal. Two experiments were carried out: In the first one, the objective was to compare the attractiveness and palatability of liquid hydrolysates compared to fishmeal, for which six experimental diets were formulated containing 10% fishmeal inclusion (FM; positive control), 5% inclusion of liquid porcine mucosa protein hydrolysate (PMH), 5% inclusion of liquid chicken protein hydrolysate (CPH) and 5% inclusion of a blend of liquid chicken protein hydrolysate and liquid porcine mucosa protein hydrolysate (CPH+PMH), 5% inclusion of a Scanbio commercial hydrolysate (SCH) and 5% inclusion of a VNF commercial hydrolysate (VFH). Twelve fingerlings (5.51 ± 0.41g) were distributed in 12 aquariums with a capacity of 22 liters, and the animals were fed six times a day, by means of a previous and random selection of the offered diets. Eight pellets were offered per feed and the following behaviors were verified in the three-minute filming: time to capture the first pellet, number of rejections, number of approaches without pellet capture, and number of pellets consumed. To calculate the palatability index (PI) the equation was used: PI = ((R-C)/(R+C))*100 (where R is the number of pellets consumed of the feed tested and C is the number of pellets consumed of the control feed. It was found that the diet containing porcine mucosa protein hydrolysate (PMH) with an index of 8.22% and VNF commercial hydrolysate (VFH) with an index of 0.61% have a positive palatability index in relation to the positive control (FM), the other foods obtained negative index (SCH -0.78%, CPH-3.16%, and PMH+CPH -3.32%). Thus, it can be considered that the liquid hydrolysates tested, according to the palatability index, are satisfactory substitutes, in terms of palatability, for fish meal. The second experiment was carried out with the objective of comparing the attractiveness and palatability of dry protein hydrolysates (chicken protein hydrolysate and tilapia protein hydrolysate), whole protein (viscera meal), and the amino acids DL-methionine and monosodium glutamate, in comparison with fish meal in the diet of dourado (Salminus brasiliensis). Six experimental diets were formulated containing: 10% inclusion of tilapia meal (TM; positive control), 10% inclusion of chicken offal meal (COM), 10% inclusion of chicken protein hydrolysate (CPH), 10 % inclusion of tilapia protein hydrolysate (TPH), 6% inclusion of DL-methionine and 6% inclusion of monosodium glutamate. Twelve fingerlings (8.33 ± 1.81 g) were distributed in 12 aquariums with a capacity of 22 liters, the animals were fed six times a day, by means of a previous and random selection of the offered diets. Fifteen pellets were offered per feed and the following behaviors were observed in the three-minute filming: time to capture the first pellet, number of pellet rejections, number of approaches without pellet capture, and number of pellets consumed. Among the diets offered, three feeds reached a positive index in relation to the positive control (TM), Chicken Protein Hydrolysate (CPH) with an index of 7.86%, Tilapia Protein Hydrolysate (TPH) with an index of 7.82%, and Viscera Meal (VM) with an index of 0.89%, the other foods had a negative index, Methionine (MET) with an index of -34.44% and Glutamine (GLU) with an index of -35.48%. Feeds with the inclusion of protein hydrolysates (CPH, TPH), tilapia meal, and viscera meal showed statistical differences (P>0.05) in relation to diets containing the inclusion of DL-methionine and glutamic acid. It is concluded that the tested dry hydrolysates and the viscera meal are favorable substitutes in relation to meal and fish for dourado (Salminus brasiliensis). Finally, mathematical modeling was carried out for the attractiveness and palatability of dourado. The proposed model (IAP) took into account more behaviors, different from the equation used previously (PI). The parameters used were: total capture time of the pellets offered, time of capture of the first pellet, amount of pellet ingestion, and amount of pellet rejection. To evaluate the equation, experimental data from Chapters 1 and 2 of this work were used. Changes were observed in the IAP, in relation to the equation proposed above. The feed containing the Scanbio commercial hydrolysate PI negative (-0.78%), with the equation proposed in this work, occupies the second place of preference (26.96%). The experimental data contained in Chapter 2 remained with a statistical difference, however, there was a change in the order of preference. The positive control diet (TM) had a neutral palatability index (0.00%) in the previous equation, and it has 57.16% of IAP in the proposed equation, moving from the fourth to the third position in preference. The mathematical model IAP found proved to be efficient for the experimental data referring to studies of attractiveness and palatability carried out with dourado.